Perspectives of breeding fungal diseases resistant cultivars of nectarine (Prunus persica (L.) Batsch. subsp. nectarina (Ait.) Shof.) - Є. П. Шоферістов; С. Ю. Цюпка; Ю. О. Іващенко (Plant Varieties Studying and Protection)
There are allocated some forms of distant hybrids with weak degree of fungal diseases lesion (Taphrina deformans (Berk.) Tul., Sphaerotheca pannosa (Lev.) var. persicae Woron., Clasterosporium carpophilum Aderh., Monilia cinerea Bonord. и Monilia fructigena Fr.) that are of practical interest for breeding such cultivars of peach and nectarine that will resist these pathogens.